Composite board based on heavy calcium carbonate and processing technology thereof

By pretreating and surface treatment of heavy calcium carbonate, combined with modified calcium carbonate and dendritic fibrous calcium carbonate, the composite material is prepared by in-situ polymerization method, which solves the shortcomings in mechanical and flame retardant properties of existing PVC composite sheets and achieves the performance improvement of composite sheets.

CN119552460AInactive Publication Date: 2025-03-04DEXING MINGYUAN CHEM MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411784229.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing PVC composite sheets with heavy calcium carbonate as filler have shortcomings in mechanical properties and flame retardant properties, making it difficult to meet higher application needs.

Method used

By pretreating and surface treatment of heavy calcium carbonate, its dispersion performance in the polyvinyl chloride matrix is ​​improved, and combined with modified calcium carbonate and dendritic fibrous calcium carbonate, the composite material is prepared by in-situ polymerization to improve its mechanical and flame retardant properties.

Benefits of technology

The tensile strength and bending strength of composite sheets are significantly improved, while improving their flame retardant properties, making them exhibit excellent mechanical and flame retardant properties in applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a composite board based on heavy calcium carbonate and a processing technology of the composite board, and relates to the technical field of composite boards. The processing technology comprises the following steps: sequentially adding 100-120 parts of polyvinyl chloride, 80-100 parts of a heavy calcium carbonate composite material, 16-20 parts of modified calcium carbonate, 0.3-0.6 part of stearic acid, 0.15-0.3 part of polyethylene wax, 0.6-1.2 parts of oxidized polyethylene, 1-2 parts of epoxidized soybean oil, 3.5-7 parts of a methacrylic acid polyvinyl chloride processing aid and 6-12 parts of chlorinated polyethylene into a mixing machine, mixing for 20-30 minutes, and carrying out melt blending, and performing mold extrusion and cooling to obtain the composite board.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite board materials, in particular to a composite board material based on heavy calcium carbonate and a processing technology thereof. Background Art

[0002] With the continuous development of the plastics industry, polyvinyl chloride (PVC) composite materials are widely used in the fields of construction, transportation, home furnishing, etc. due to their excellent processing performance, good corrosion resistance and cost advantages. In these applications, heavy calcium carbonate (CaCO3) is widely used as a common filler in the preparation of PVC composite sheets. Heavy calcium carbonate can not only reduce material costs, but also improve certain physical properties, such as improving the rigidity and dimensional stability of the material. However, the PVC composite sheets with heavy calcium carbonate as filler in the prior art still have certain deficiencies in some key properties, especially in mechanical properties and flame retardant properties.

[0003] First, the addition of heavy calcium carbonate has limited effect on the mechanical properties of PVC composites. Although it can improve the rigidity of the composite, due to its large particle size, low surface activity, and poor dispersion in the polymer matrix, the composite has low toughness and tensile strength, which makes it prone to cracks and fractures, especially under long-term use or stress conditions.

[0004] Secondly, heavy calcium carbonate has little effect on improving the flame retardant properties of composite panels. Although heavy calcium carbonate can act as a physical barrier to a certain extent, it does not have strong flame retardant properties and it is difficult to effectively improve the flame retardant level of the material. Due to the inherent flammability of polyvinyl chloride, when a fire occurs, composite materials containing heavy calcium carbonate tend to burn quickly and release toxic gases, seriously affecting safety.

[0005] Therefore, although heavy calcium carbonate has a certain application as a filler in PVC composite materials, its deficiencies in mechanical properties and flame retardancy limit its further development and widespread application. In order to solve these problems, researchers need to explore more optimized fillers and processing techniques to improve the comprehensive properties of composite materials. Summary of the invention

[0006] The purpose of the present invention is to provide a composite board based on heavy calcium carbonate and a processing method thereof to solve the problems raised in the prior art.

[0007] To achieve the above purpose, the present invention provides the following technical solutions

[0008] A composite board based on heavy calcium carbonate, wherein the raw material components of the composite board based on heavy calcium carbonate include: 100-120 parts of polyvinyl chloride, 80-100 parts of heavy calcium carbonate composite material, 16-20 parts of modified calcium carbonate, 0.3-0.6 parts of stearic acid, 0.15-0.3 parts of polyethylene wax, 0.6-1.2 parts of oxidized polyethylene, 1-2 parts of epoxy soybean oil, 3.5-7 parts of methacrylic acid polyvinyl chloride processing aid, and 6-12 parts of chlorinated polyethylene.

[0009] Furthermore, the preparation method of the heavy calcium carbonate composite material comprises the following steps:

[0010] Add heavy calcium carbonate to a mixed solution of 1 mol / L sodium hydroxide and 0.1 mol / L sodium carbonate, stir at room temperature for 2-3 hours, filter, collect the slurry, wash the slurry with distilled water, and vacuum dry at 125-130° C. for 8-10 hours to obtain pretreated heavy calcium carbonate;

[0011] Add isopropyl trioleyl titanate to ethanol, stir evenly, add toluene suspension of pretreated heavy calcium carbonate under nitrogen atmosphere, heat to 75-80°C for reaction for 50-60min, cool to room temperature, centrifuge, vacuum dry at 70-75°C for 18-20h, extract with toluene Soxhlet extractor for 18-20h, and finally vacuum dry the remaining product at 70-75°C for 24h to obtain surface-treated heavy calcium carbonate;

[0012] The surface treated heavy calcium carbonate is dispersed in deionized water, and liquid vinyl chloride, polyvinyl acetate, carboxypropyl cellulose, azobisisobutyronitrile and di(2-ethylhexyl) peroxydicarbonate are added in sequence, and the reaction is carried out at 3-3.2 MPa and 54-54.2° C. until the conversion rate of the liquid vinyl chloride reaches 85%, thereby obtaining a heavy calcium carbonate composite material.

[0013] Furthermore, during the preparation of the pretreated heavy calcium carbonate, the solid content of the heavy calcium carbonate during the pretreatment process is 10-12 wt%.

[0014] Furthermore, in the preparation process of the surface-treated heavy calcium carbonate, the mass ratio of pretreated heavy calcium carbonate: isopropyl trioleate acyloxy titanate is 100:(5-6).

[0015] Furthermore, in the preparation process of the heavy calcium carbonate composite material, the proportions of each raw material component by mass fraction include: 100 parts of liquid vinyl chloride, 5-7.5 parts of surface-treated heavy calcium carbonate, 5-7.5 parts of polyvinyl acetate, 5-7.5 parts of carboxypropyl cellulose, 0.2-0.4 parts of azobisisobutyronitrile, and 0.2-0.4 parts of di(2-ethylhexyl) peroxydicarbonate.

[0016] Furthermore, the preparation method of the modified calcium carbonate comprises the following steps:

[0017] Adding hexadecyltrimethylammonium bromide to a mixture of glycerol and water in a volume ratio of 1:4 to obtain a hexadecyltrimethylammonium bromide solution; adding 0.5 mol / L sodium carbonate solution and 0.5 mol / L sodium chloride solution to the hexadecyltrimethylammonium bromide solution under stirring, heating to 80-82°C for reaction for 6-7 hours, cooling to room temperature, filtering, collecting precipitates, washing the precipitates with deionized water and anhydrous ethanol, and vacuum drying at 75-80°C for 8-10 hours to obtain fibrous calcium carbonate;

[0018] The fibrous calcium carbonate is ultrasonically dispersed in deionized water, and sodium stannate and zinc sulfate heptahydrate are added under stirring, and the mixture is heated to 80-82°C for reaction for 4-5 hours, cooled to room temperature, filtered, and the precipitate is collected, and the precipitate is washed with deionized water and anhydrous ethanol, and vacuum dried at 75-80°C for 8-10 hours to obtain coated calcium carbonate; the coated calcium carbonate is ultrasonically dispersed in deionized water, 2-carboxyethylphenylphosphinic acid is added, and the mixture is heated to 90-92°C for reaction for 12-12.5 hours, filtered, and the precipitate is collected, and the precipitate is washed with deionized water and sewage ethanol, and vacuum dried at 75-80°C for 8-10 hours to obtain modified calcium carbonate.

[0019] Furthermore, in the preparation process of the fibrous calcium carbonate, the concentration of the cetyltrimethylammonium bromide solution is 2.2-2.4 g / L; and the volume ratio of the cetyltrimethylammonium bromide solution: the sodium carbonate solution: the calcium chloride solution is 250:4:4.

[0020] Furthermore, in the preparation process of the coated calcium carbonate, the mass ratio of fibrous calcium carbonate: sodium stannate: zinc sulfate heptahydrate is 10:(1-2):(1-2); in the preparation process of modified calcium carbonate, the mass ratio of coated calcium carbonate:2-carboxyethylphenylphosphinic acid is (5-10):(3-5).

[0021] A processing technology for a composite board based on heavy calcium carbonate comprises the following steps: sequentially adding polyvinyl chloride, heavy calcium carbonate composite material, modified calcium carbonate, stearic acid, polyethylene wax, oxidized polyethylene, epoxy soybean oil, methacrylic acid polyvinyl chloride processing aid, and chlorinated polyethylene into a mixer, mixing for 20-30 minutes, melt blending, extruding through a mold, and cooling to obtain a composite board.

[0022] Furthermore, during the die extrusion process, the extruder barrel temperature is 175-190°C, and the die head heating temperature is 170-190°C.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention firstly pre-treats the surface of heavy calcium carbonate with sodium hydroxide, promotes the formation of hydroxyl groups on the surface of heavy calcium carbonate, greatly improves the grafting rate of isopropyl trioleyloxy titanate on its surface, and improves its dispersion performance in the resin matrix during the in-situ polymerization process. In the presence of pre-treated heavy calcium carbonate, vinyl chloride is used as a dispersed phase, deionized water is used as a continuous phase, polyvinyl acetate and hydroxypropyl cellulose are used as suspension aids, azobisisobutyronitrile and di(2-ethylhexyl) peroxydicarbonate are used as initiators, and a composite material of polyvinyl chloride-heavy calcium carbonate is prepared by in-situ polymerization, thereby improving the dispersion performance of heavy calcium carbonate in the polyvinyl chloride matrix. Due to the restriction of heavy calcium carbonate nanoparticles on the chain segment and long-range chain mobility of the polyvinyl chloride phase, the glass transition temperature and thermal decomposition temperature of the polyvinyl chloride phase in the polyvinyl chloride / heavy calcium carbonate nanocomposite material move to the high temperature direction, thereby improving the tensile strength of the composite plate, and the heavy calcium carbonate nanoparticles act as stress concentrators, further improving the bending strength of the composite plate.

[0025] 2. In order to further broaden the application scenarios of composite boards, dendritic fibrous calcium carbonate was prepared, and dendritic fibrous calcium carbonate coated with hydroxystannate zinc was further prepared in hexadecyltrimethylammonium bromide / glycerol aqueous solution and pure water solution, and further surface-modified with 2-carboxyethylphenylphosphinic acid. The surface modification of 2-carboxyethylphenylphosphinic acid greatly improved its dispersion performance in polyvinyl chloride, and at the same time, it can avoid the occurrence of self-agglomeration. The dendritic structure of the dendritic fibrous calcium carbonate is used to distinguish it from traditional block calcium carbonate. While ensuring its excellent dispersion performance, the surface modification of 2-carboxyethylphenylphosphinic acid reduces the influence of the resin oxygen index and mechanical properties, perfectly balancing the flame retardant properties and mechanical properties, so that the composite board has excellent mechanical properties and excellent flame retardant properties. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the following examples, the specification of heavy calcium carbonate is 3000-4000 mesh, the model of methacrylate polyvinyl chloride processing aid is Japan Mitsubishi P-533J, and the other raw materials are commercially available.

[0028] Example 1: A processing technology for a composite plate based on heavy calcium carbonate: S11: Add heavy calcium carbonate to a mixed solution of 1 mol / L sodium hydroxide and 0.1 mol / L sodium carbonate, stir at room temperature for 2 hours, filter, collect slurry, wash the slurry with distilled water, and vacuum dry at 125° C. for 8 hours to obtain pretreated heavy calcium carbonate; the solid content of heavy calcium carbonate during the pretreatment process is 10wt%;

[0029] S12: Add 5 g of isopropyl trioleyl titanate to ethanol, stir evenly, add a toluene suspension containing 100 g of pretreated heavy calcium carbonate under a nitrogen atmosphere, heat to 75°C for reaction for 50 min, cool to room temperature, centrifuge, vacuum dry at 70°C for 18 h, extract with a toluene Soxhlet extractor for 18 h, and finally vacuum dry the remaining product at 70°C for 24 h to obtain surface-treated heavy calcium carbonate;

[0030] S13: Dispersing 5 parts of surface-treated heavy calcium carbonate in deionized water, adding 100 parts of liquid vinyl chloride, 5 parts of polyvinyl acetate, 5 parts of carboxypropyl cellulose, c.2 parts of azobisisobutyronitrile, and 0.2 parts of di(2-ethylhexyl) peroxydicarbonate in sequence, reacting at 3MPa and 54°C until the conversion rate of liquid vinyl chloride reaches 85%, to obtain a heavy calcium carbonate composite material;

[0031] S21: Add 2.2 g of hexadecyltrimethylammonium bromide to 1 L of a mixture of glycerol and water in a volume ratio of 1:4 to obtain a hexadecyltrimethylammonium bromide solution; under stirring, add 4 mL of 0.5 mol / L sodium carbonate solution and 4 mL of 0.5 mol / L sodium chloride solution to 250 mL of the hexadecyltrimethylammonium bromide solution, heat to 80°C for reaction for 6 h, cool to room temperature, filter, collect the precipitate, wash the precipitate with deionized water and anhydrous ethanol, and vacuum dry at 75°C for 8 h to obtain fibrous calcium carbonate;

[0032] S22: ultrasonically disperse 10g of fibrous calcium carbonate in deionized water, add 1g of sodium stannate and 1g of zinc sulfate heptahydrate under stirring, heat to 80°C for reaction for 4h, cool to room temperature, filter, collect precipitate, wash precipitate with deionized water and anhydrous ethanol, and vacuum dry at 75°C for 8-10h to obtain coated calcium carbonate; ultrasonically disperse 10g of coated calcium carbonate in deionized water, add 3g of 2-carboxyethylphenylphosphinic acid, heat to 90°C for reaction for 12h, filter, collect precipitate, wash precipitate with deionized water and sewage ethanol, and vacuum dry at 75°C for 8h to obtain modified calcium carbonate;

[0033] S3: Add 120 parts of polyvinyl chloride, 80 parts of heavy calcium carbonate composite material, 16 parts of modified calcium carbonate, 0.4 parts of stearic acid, 0.2 parts of polyethylene wax, 0.8 parts of oxidized polyethylene, 1 part of epoxy soybean oil, 4 parts of methacrylate polyvinyl chloride processing aid, and 8 parts of chlorinated polyethylene into a mixer in sequence, mix for 20 minutes, melt blend, extrude into a mold, and cool to obtain a composite sheet.

[0034] Example 2: A processing technology for a composite plate based on heavy calcium carbonate: S11: adding heavy calcium carbonate to a mixed solution of 1 mol / L sodium hydroxide and 0.1 mol / L sodium carbonate, stirring at room temperature for 2 hours, filtering, collecting the slurry, washing the slurry with distilled water, and vacuum drying at 125° C. for 8 hours to obtain pretreated heavy calcium carbonate; the solid content of the heavy calcium carbonate during the pretreatment process is 10wt%;

[0035] S12: Add 5 g of isopropyl trioleyl titanate to ethanol, stir evenly, add a toluene suspension containing 100 g of pretreated heavy calcium carbonate under a nitrogen atmosphere, heat to 75°C for reaction for 50 min, cool to room temperature, centrifuge, vacuum dry at 70°C for 18 h, extract with a toluene Soxhlet extractor for 18 h, and finally vacuum dry the remaining product at 70°C for 24 h to obtain surface-treated heavy calcium carbonate;

[0036] S13: Dispersing 7.5 parts of surface-treated heavy calcium carbonate in deionized water, adding 100 parts of liquid vinyl chloride, 5 parts of polyvinyl acetate, 5 parts of carboxypropyl cellulose, 0.2 parts of azobisisobutyronitrile, and 0.2 parts of di(2-ethylhexyl) peroxydicarbonate in sequence, reacting at 3MPa and 54°C until the conversion rate of liquid vinyl chloride reaches 85%, to obtain a heavy calcium carbonate composite material;

[0037] S21: Add 2.2 g of hexadecyltrimethylammonium bromide to 1 L of a mixture of glycerol and water in a volume ratio of 1:4 to obtain a hexadecyltrimethylammonium bromide solution; under stirring, add 4 mL of 0.5 mol / L sodium carbonate solution and 4 mL of 0.5 mol / L sodium chloride solution to 250 mL of the hexadecyltrimethylammonium bromide solution, heat to 80°C for reaction for 6 h, cool to room temperature, filter, collect the precipitate, wash the precipitate with deionized water and anhydrous ethanol, and vacuum dry at 75°C for 8 h to obtain fibrous calcium carbonate;

[0038] S22: ultrasonically disperse 10g of fibrous calcium carbonate in deionized water, add 1g of sodium stannate and 1g of zinc sulfate heptahydrate under stirring, heat to 80°C for reaction for 4h, cool to room temperature, filter, collect precipitate, wash precipitate with deionized water and anhydrous ethanol, and vacuum dry at 75°C for 8-10h to obtain coated calcium carbonate; ultrasonically disperse 10g of coated calcium carbonate in deionized water, add 3g of 2-carboxyethylphenylphosphinic acid, heat to 90°C for reaction for 12h, filter, collect precipitate, wash precipitate with deionized water and sewage ethanol, and vacuum dry at 75°C for 8h to obtain modified calcium carbonate;

[0039] S3: Add 120 parts of polyvinyl chloride, 80 parts of heavy calcium carbonate composite material, 16 parts of modified calcium carbonate, 0.4 parts of stearic acid, 0.2 parts of polyethylene wax, 0.8 parts of oxidized polyethylene, 1 part of epoxy soybean oil, 4 parts of methacrylate polyvinyl chloride processing aid, and 8 parts of chlorinated polyethylene into a mixer in sequence, mix for 20 minutes, melt blend, extrude into a mold, and cool to obtain a composite sheet.

[0040] Example 3: A processing technology for a composite plate based on heavy calcium carbonate: S11: adding heavy calcium carbonate to a mixed solution of 1 mol / L sodium hydroxide and 0.1 mol / L sodium carbonate, stirring at room temperature for 2 hours, filtering, collecting slurry, washing the slurry with distilled water, and vacuum drying at 125° C. for 8 hours to obtain pretreated heavy calcium carbonate; the solid content of the heavy calcium carbonate during the pretreatment process is 10wt%;

[0041] S12: Add 5 g of isopropyl trioleyl titanate to ethanol, stir evenly, add a toluene suspension containing 100 g of pretreated heavy calcium carbonate under a nitrogen atmosphere, heat to 75°C for reaction for 50 min, cool to room temperature, centrifuge, vacuum dry at 70°C for 18 h, extract with a toluene Soxhlet extractor for 18 h, and finally vacuum dry the remaining product at 70°C for 24 h to obtain surface-treated heavy calcium carbonate;

[0042] S13: Dispersing 7.5 parts of surface-treated heavy calcium carbonate in deionized water, adding 100 parts of liquid vinyl chloride, 5 parts of polyvinyl acetate, 5 parts of carboxypropyl cellulose, 0.2 parts of azobisisobutyronitrile, and 0.2 parts of di(2-ethylhexyl) peroxydicarbonate in sequence, reacting at 3MPa and 54°C until the conversion rate of liquid vinyl chloride reaches 85%, to obtain a heavy calcium carbonate composite material;

[0043] S21: Add 2.2 g of hexadecyltrimethylammonium bromide to 1 L of a mixture of glycerol and water in a volume ratio of 1:4 to obtain a hexadecyltrimethylammonium bromide solution; under stirring, add 4 mL of 0.5 mol / L sodium carbonate solution and 4 mL of 0.5 mol / L sodium chloride solution to 250 mL of the hexadecyltrimethylammonium bromide solution, heat to 80°C for reaction for 6 h, cool to room temperature, filter, collect the precipitate, wash the precipitate with deionized water and anhydrous ethanol, and vacuum dry at 75°C for 8 h to obtain fibrous calcium carbonate;

[0044] S22: ultrasonically disperse 10g of fibrous calcium carbonate in deionized water, add 2g of sodium stannate and 2g of zinc sulfate heptahydrate under stirring, heat to 80°C for reaction for 4h, cool to room temperature, filter, collect precipitate, wash precipitate with deionized water and anhydrous ethanol, and vacuum dry at 75°C for 8-10h to obtain coated calcium carbonate; ultrasonically disperse 10g of coated calcium carbonate in deionized water, add 5g of 2-carboxyethylphenylphosphinic acid, heat to 90°C for reaction for 12h, filter, collect precipitate, wash precipitate with deionized water and sewage ethanol, and vacuum dry at 75°C for 8h to obtain modified calcium carbonate;

[0045] S3: Add 120 parts of polyvinyl chloride, 80 parts of heavy calcium carbonate composite material, 16 parts of modified calcium carbonate, 0.4 parts of stearic acid, 0.2 parts of polyethylene wax, 0.8 parts of oxidized polyethylene, 1 part of epoxy soybean oil, 4 parts of methacrylate polyvinyl chloride processing aid, and 8 parts of chlorinated polyethylene into a mixer in sequence, mix for 20 minutes, melt blend, extrude into a mold, and cool to obtain a composite sheet.

[0046] Example 4: A processing technology for a composite plate based on heavy calcium carbonate: S11: adding heavy calcium carbonate to a mixed solution of 1 mol / L sodium hydroxide and 0.1 mol / L sodium carbonate, stirring at room temperature for 2 hours, filtering, collecting the slurry, washing the slurry with distilled water, and vacuum drying at 125° C. for 8 hours to obtain pretreated heavy calcium carbonate; the solid content of the heavy calcium carbonate during the pretreatment process is 10wt%;

[0047] S12: Add 5 g of isopropyl trioleyl titanate to ethanol, stir evenly, add a toluene suspension containing 100 g of pretreated heavy calcium carbonate under a nitrogen atmosphere, heat to 75°C for reaction for 50 min, cool to room temperature, centrifuge, vacuum dry at 70°C for 18 h, extract with a toluene Soxhlet extractor for 18 h, and finally vacuum dry the remaining product at 70°C for 24 h to obtain surface-treated heavy calcium carbonate;

[0048] S13: Dispersing 7.5 parts of surface-treated heavy calcium carbonate in deionized water, adding 100 parts of liquid vinyl chloride, 5 parts of polyvinyl acetate, 5 parts of carboxypropyl cellulose, 0.2 parts of azobisisobutyronitrile, and 0.2 parts of di(2-ethylhexyl) peroxydicarbonate in sequence, reacting at 3MPa and 54°C until the conversion rate of liquid vinyl chloride reaches 85%, to obtain a heavy calcium carbonate composite material;

[0049] S21: Add 2.2 g of hexadecyltrimethylammonium bromide to 1 L of a mixture of glycerol and water in a volume ratio of 1:4 to obtain a hexadecyltrimethylammonium bromide solution; under stirring, add 4 mL of 0.5 mol / L sodium carbonate solution and 4 mL of 0.5 mol / L sodium chloride solution to 250 mL of the hexadecyltrimethylammonium bromide solution, heat to 80°C for reaction for 6 h, cool to room temperature, filter, collect the precipitate, wash the precipitate with deionized water and anhydrous ethanol, and vacuum dry at 75°C for 8 h to obtain fibrous calcium carbonate;

[0050] S22: ultrasonically disperse 10g of fibrous calcium carbonate in deionized water, add 2g of sodium stannate and 2g of zinc sulfate heptahydrate under stirring, heat to 80°C for reaction for 4h, cool to room temperature, filter, collect precipitate, wash precipitate with deionized water and anhydrous ethanol, and vacuum dry at 75°C for 8-10h to obtain coated calcium carbonate; ultrasonically disperse 10g of coated calcium carbonate in deionized water, add 5g of 2-carboxyethylphenylphosphinic acid, heat to 90°C for reaction for 12h, filter, collect precipitate, wash precipitate with deionized water and sewage ethanol, and vacuum dry at 75°C for 8h to obtain modified calcium carbonate;

[0051] S3: Add 100 parts of polyvinyl chloride, 100 parts of heavy calcium carbonate composite material, 16 parts of modified calcium carbonate, 0.4 parts of stearic acid, 0.2 parts of polyethylene wax, 0.8 parts of oxidized polyethylene, 1 part of epoxy soybean oil, 4 parts of methacrylate polyvinyl chloride processing aid, and 8 parts of chlorinated polyethylene into a mixer in sequence, mix for 20 minutes, melt blend, extrude into a mold, and cool to obtain a composite sheet.

[0052] Example 5: A processing technology for a composite plate based on heavy calcium carbonate: S11: adding heavy calcium carbonate to a mixed solution of 1 mol / L sodium hydroxide and 0.1 mol / L sodium carbonate, stirring at room temperature for 2 hours, filtering, collecting the slurry, washing the slurry with distilled water, and vacuum drying at 125° C. for 8 hours to obtain pretreated heavy calcium carbonate; the solid content of the heavy calcium carbonate during the pretreatment process is 10wt%;

[0053] S12: Add 5 g of isopropyl trioleyl titanate to ethanol, stir evenly, add a toluene suspension containing 100 g of pretreated heavy calcium carbonate under a nitrogen atmosphere, heat to 75°C for reaction for 50 min, cool to room temperature, centrifuge, vacuum dry at 70°C for 18 h, extract with a toluene Soxhlet extractor for 18 h, and finally vacuum dry the remaining product at 70°C for 24 h to obtain surface-treated heavy calcium carbonate;

[0054] S13: Dispersing 7.5 parts of surface-treated heavy calcium carbonate in deionized water, adding 100 parts of liquid vinyl chloride, 5 parts of polyvinyl acetate, 5 parts of carboxypropyl cellulose, 0.2 parts of azobisisobutyronitrile, and 0.2 parts of di(2-ethylhexyl) peroxydicarbonate in sequence, reacting at 3MPa and 54°C until the conversion rate of liquid vinyl chloride reaches 85%, to obtain a heavy calcium carbonate composite material;

[0055] S21: Add 2.2 g of hexadecyltrimethylammonium bromide to 1 L of a mixture of glycerol and water in a volume ratio of 1:4 to obtain a hexadecyltrimethylammonium bromide solution; under stirring, add 4 mL of 0.5 mol / L sodium carbonate solution and 4 mL of 0.5 mol / L sodium chloride solution to 250 mL of the hexadecyltrimethylammonium bromide solution, heat to 80°C for reaction for 6 h, cool to room temperature, filter, collect the precipitate, wash the precipitate with deionized water and anhydrous ethanol, and vacuum dry at 75°C for 8 h to obtain fibrous calcium carbonate;

[0056] S22: ultrasonically disperse 10g of fibrous calcium carbonate in deionized water, add 2g of sodium stannate and 2g of zinc sulfate heptahydrate under stirring, heat to 80°C for reaction for 4h, cool to room temperature, filter, collect precipitate, wash precipitate with deionized water and anhydrous ethanol, and vacuum dry at 75°C for 8-10h to obtain coated calcium carbonate; ultrasonically disperse 10g of coated calcium carbonate in deionized water, add 5g of 2-carboxyethylphenylphosphinic acid, heat to 90°C for reaction for 12h, filter, collect precipitate, wash precipitate with deionized water and sewage ethanol, and vacuum dry at 75°C for 8h to obtain modified calcium carbonate;

[0057] S3: Add 100 parts of polyvinyl chloride, 100 parts of heavy calcium carbonate composite material, 20 parts of modified calcium carbonate, 0.4 parts of stearic acid, 0.2 parts of polyethylene wax, 0.8 parts of oxidized polyethylene, 1 part of epoxy soybean oil, 4 parts of methacrylate polyvinyl chloride processing aid, and 8 parts of chlorinated polyethylene into a mixer in sequence, mix for 20 minutes, melt blend, extrude into a mold, and cool to obtain a composite sheet.

[0058] Comparative Example 1: A processing technology for a composite plate based on heavy calcium carbonate: S12: Add 3 g of isopropyl trioleyl titanate to ethanol, stir evenly, add a toluene suspension containing 100 g of pretreated heavy calcium carbonate under a nitrogen atmosphere, heat to 90°C for reaction for 700 min, cool to room temperature, centrifuge, vacuum dry at 70°C for 18 h, extract with a toluene Soxhlet extractor for 18 h, and finally vacuum dry the remaining product at 70°C for 24 h to obtain surface-treated heavy calcium carbonate;

[0059] The remaining steps are the same as those in Example 1.

[0060] Comparative Example 2: A processing technology for a composite board based on heavy calcium carbonate: S13: Disperse 10 parts of surface-treated heavy calcium carbonate in deionized water, add 100 parts of liquid vinyl chloride, 5 parts of polyvinyl acetate, 5 parts of carboxypropyl cellulose, 0.2 parts of azobisisobutyronitrile, and 0.2 parts of di(2-ethylhexyl) peroxydicarbonate in sequence, and react at 3MPa and 54°C until the conversion rate of liquid vinyl chloride reaches 85%, to obtain a heavy calcium carbonate composite material;

[0061] The remaining steps are the same as those in Example 1.

[0062] Comparative Example 3: A processing technology for a composite plate based on heavy calcium carbonate: S11: Add heavy calcium carbonate to a mixed solution of 1 mol / L sodium hydroxide and 0.1 mol / L sodium carbonate, stir at room temperature for 2 hours, filter, collect the slurry, wash the slurry with distilled water, and vacuum dry at 125° C. for 8 hours to obtain pretreated heavy calcium carbonate; the solid content of the heavy calcium carbonate during the pretreatment process is 10wt%;

[0063] S12: Add 5 g of isopropyl trioleyl titanate to ethanol, stir evenly, add a toluene suspension containing 100 g of pretreated heavy calcium carbonate under a nitrogen atmosphere, heat to 75°C for reaction for 50 min, cool to room temperature, centrifuge, vacuum dry at 70°C for 18 h, extract with a toluene Soxhlet extractor for 18 h, and finally vacuum dry the remaining product at 70°C for 24 h to obtain surface-treated heavy calcium carbonate;

[0064] S13: Dispersing 5 parts of surface-treated heavy calcium carbonate in deionized water, adding 100 parts of liquid vinyl chloride, 5 parts of polyvinyl acetate, 5 parts of carboxypropyl cellulose, 0.2 parts of azobisisobutyronitrile, and 0.2 parts of di(2-ethylhexyl) peroxydicarbonate in sequence, reacting at 3 MPa and 54° C. until the conversion rate of liquid vinyl chloride reaches 85%, to obtain a heavy calcium carbonate composite material;

[0065] S21: Add 1 mol of calcium chloride and 5 mol of urea to deionized water, heat to 80°C for 6 hours, cool to room temperature, filter, collect the precipitate, wash the precipitate with deionized water and ethanol, and vacuum dry at 75°C for 8 hours to obtain cube-shaped calcium carbonate;

[0066] S22: ultrasonically disperse 10g of cube calcium carbonate in deionized water, add 1g of sodium stannate and 1g of zinc sulfate heptahydrate under stirring, heat to 80°C for reaction for 4h, cool to room temperature, filter, collect precipitate, wash precipitate with deionized water and anhydrous ethanol, vacuum dry at 75°C for 8-10h to obtain coated calcium carbonate; ultrasonically disperse 10g of coated calcium carbonate in deionized water, add 3g of 2-carboxyethylphenylphosphinic acid, heat to 90°C for reaction for 12h, filter, collect precipitate, wash precipitate with deionized water and sewage ethanol, vacuum dry at 75°C for 8h to obtain modified calcium carbonate;

[0067] S3: Add 120 parts of polyvinyl chloride, 80 parts of heavy calcium carbonate composite material, 16 parts of modified calcium carbonate, 0.4 parts of stearic acid, 0.2 parts of polyethylene wax, 0.8 parts of oxidized polyethylene, 1 part of epoxy soybean oil, 4 parts of methacrylate polyvinyl chloride processing aid, and 8 parts of chlorinated polyethylene into a mixer in sequence, mix for 20 minutes, melt blend, extrude into a mold, and cool to obtain a composite sheet.

[0068] Comparative Example 4: A processing technology for a composite board based on heavy calcium carbonate: S22: Ultrasonic dispersion of 10 g of fibrous calcium carbonate in deionized water, adding 1 g of sodium stannate and 1 g of zinc sulfate heptahydrate under stirring, heating to 80°C for reaction for 4 h, cooling to room temperature, filtering, collecting precipitates, washing the precipitates with deionized water and anhydrous ethanol, and vacuum drying at 75°C for 8-10 h to obtain modified calcium carbonate;

[0069] The remaining steps are the same as those in Example 1.

[0070] Experiment: Flame retardant performance test: LOI value test is carried out according to ASTM D2863, and the test sample size is 130mm×6mm×3mm;

[0071] Mechanical properties test: According to ISO 527-2012 and 178-2001, the tensile strength and flexural strength of the composite sheet were tested using a universal testing machine. The tensile strength test sample size was 150 mm × 20 mm × 3 mm dumbbell-shaped, and the flexural strength test sample size was 80 mm × 10 mm × 3 mm.

[0072] The experimental data are shown in Table 1 below.

[0073] Table 1 Composite board performance test data table

[0074] LOI / % <![CDATA[Tensile strength / MPa > <![CDATA[Flexural strength / MPa > Example 1 34.2 43.2 56.7 Example 2 34.3 44.6 57.2 Example 3 35.6 45.0 57.8 Example 4 35.5 47.2 58.8 Example 5 36.8 47.0 58.7 Comparative Example 1 34.1 41.0 51.5 Comparative Example 2 34.2 39.7 49.5 Comparative Example 3 30.2 41.5 50.2 Comparative Example 4 33.5 40.7 50.9

[0075] Conclusion: The composite board prepared by the present invention has excellent mechanical properties and flame retardant properties.

[0076] In the preparation process of surface-treated heavy calcium carbonate in Comparative Example 1, too little isopropyl trioleyl titanate was added, and the reaction temperature was too high and the time was too long, resulting in a decrease in the surface grafting rate of the surface-treated heavy calcium carbonate, poor dispersion during the subsequent in-situ polymerization of vinyl chloride, and reduced mechanical properties of the composite board.

[0077] In the preparation process of the heavy calcium carbonate composite material of Comparative Example 2, the amount of surface-treated heavy calcium carbonate added was increased, resulting in a decrease in the mechanical properties of the composite board.

[0078] In Comparative Example 3, calcium chloride and urea are used to prepare block calcium carbonate as the raw material for preparing modified calcium titanate. The lack of dendritic fibrous calcium carbonate as the raw material leads to reduced efficiency of coating modification and grafting modification, reduced interfacial effect in the resin matrix, and reduced flame retardant and mechanical properties of the composite board.

[0079] In the preparation process of the modified calcium carbonate in Comparative Example 4, only coating modification was performed without 2-hydroxyethylphenyl hypophosphite modification, resulting in reduced dispersion performance in the resin matrix, reduced mechanical properties, and slightly reduced flame retardant properties.

[0080] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A composite board based on heavy calcium carbonate, characterized in that: The raw material components of the composite board based on heavy calcium carbonate include: 100-120 parts of polyvinyl chloride, 80-100 parts of heavy calcium carbonate composite material, 16-20 parts of modified calcium carbonate, 0.3-0.6 parts of stearic acid, 0.15-0.3 parts of polyethylene wax, 0.6-1.2 parts of oxidized polyethylene, 1-2 parts of epoxy soybean oil, 3.5-7 parts of methacrylic acid polyvinyl chloride processing aid, and 6-12 parts of chlorinated polyethylene.

2. The composite board based on heavy calcium carbonate according to claim 1, characterized in that: The preparation method of the heavy calcium carbonate composite material comprises the following steps: Add heavy calcium carbonate to a mixed solution of 1 mol / L sodium hydroxide and 0.1 mol / L sodium carbonate, stir at room temperature for 2-3 hours, filter, collect the slurry, wash the slurry with distilled water, and vacuum dry at 125-130° C. for 8-10 hours to obtain pretreated heavy calcium carbonate; Add isopropyl trioleyl titanate to ethanol, stir evenly, add toluene suspension of pretreated heavy calcium carbonate under nitrogen atmosphere, heat to 75-80°C for reaction for 50-60min, cool to room temperature, centrifuge, vacuum dry at 70-75°C for 18-20h, extract with toluene Soxhlet extractor for 18-20h, and finally vacuum dry the remaining product at 70-75°C for 24h to obtain surface-treated heavy calcium carbonate; The surface treated heavy calcium carbonate is dispersed in deionized water, and liquid vinyl chloride, polyvinyl acetate, carboxypropyl cellulose, azobisisobutyronitrile and di(2-ethylhexyl) peroxydicarbonate are added in sequence, and the reaction is carried out at 3-3.2 MPa and 54-54.2° C. until the conversion rate of the liquid vinyl chloride reaches 85%, thereby obtaining a heavy calcium carbonate composite material.

3. The composite board based on heavy calcium carbonate according to claim 2, characterized in that: During the preparation of pretreated heavy calcium carbonate, the solid content of heavy calcium carbonate during the pretreatment process is 10-12 wt %.

4. The composite board based on heavy calcium carbonate according to claim 2, characterized in that: In the preparation process of surface-treated heavy calcium carbonate, the mass ratio of pre-treated heavy calcium carbonate to isopropyl trioleate titanate is 100:(5-6).

5. The composite board based on heavy calcium carbonate according to claim 2, characterized in that: In the preparation process of heavy calcium carbonate composite materials, the proportions of various raw material components by mass fraction include: 100 parts of liquid vinyl chloride, 5-7.5 parts of surface-treated heavy calcium carbonate, 5-7.5 parts of polyvinyl acetate, 5-7.5 parts of carboxypropyl cellulose, 0.2-0.4 parts of azobisisobutyronitrile, and 0.2-0.4 parts of di(2-ethylhexyl) peroxydicarbonate.

6. The composite board based on heavy calcium carbonate according to claim 1, characterized in that: The preparation method of the modified calcium carbonate comprises the following steps: Adding hexadecyltrimethylammonium bromide to a mixture of glycerol and water in a volume ratio of 1:4 to obtain a hexadecyltrimethylammonium bromide solution; adding 0.5 mol / L sodium carbonate solution and 0.5 mol / L sodium chloride solution to the hexadecyltrimethylammonium bromide solution under stirring, heating to 80-82° C. for reaction for 6-7 hours, cooling to room temperature, filtering, collecting precipitates, washing the precipitates with deionized water and anhydrous ethanol, and vacuum drying at 75-80° C. for 8-10 hours to obtain fibrous calcium carbonate; The fibrous calcium carbonate is ultrasonically dispersed in deionized water, and sodium stannate and zinc sulfate heptahydrate are added under stirring, and the mixture is heated to 80-82°C for reaction for 4-5 hours, cooled to room temperature, filtered, and the precipitate is collected, and the precipitate is washed with deionized water and anhydrous ethanol, and vacuum dried at 75-80°C for 8-10 hours to obtain coated calcium carbonate; the coated calcium carbonate is ultrasonically dispersed in deionized water, 2-carboxyethylphenylphosphinic acid is added, and the mixture is heated to 90-92°C for reaction for 12-12.5 hours, filtered, and the precipitate is collected, and the precipitate is washed with deionized water and sewage ethanol, and vacuum dried at 75-80°C for 8-10 hours to obtain modified calcium carbonate.

7. The composite board based on heavy calcium carbonate according to claim 6, characterized in that: In the preparation process of fibrous calcium carbonate, the concentration of hexadecyltrimethylammonium bromide solution is 2.2-2.4 g / L; the volume ratio of hexadecyltrimethylammonium bromide solution: sodium carbonate solution: calcium chloride solution is 250:4:

4.

8. The composite board based on heavy calcium carbonate according to claim 6, characterized in that: In the preparation process of coated calcium carbonate, the mass ratio of fibrous calcium carbonate: sodium stannate: zinc sulfate heptahydrate is 10:(1-2):(1-2); in the preparation process of modified calcium carbonate, the mass ratio of coated calcium carbonate: 2-carboxyethylphenylphosphinic acid is (5-10):(3-5).

9. A processing technology for a composite board based on heavy calcium carbonate according to any one of claims 1 to 8, characterized in that: The following steps are involved: Polyvinyl chloride, heavy calcium carbonate composite material, modified calcium carbonate, stearic acid, polyethylene wax, oxidized polyethylene, epoxy soybean oil, methacrylic acid polyvinyl chloride processing aid, and chlorinated polyethylene are sequentially added into a mixer, mixed for 20-30 minutes, melt-blended, extruded into a mold, and cooled to obtain a composite plate.

10. The processing technology of the composite board based on heavy calcium carbonate according to claim 9, characterized in that: During the die extrusion process, the extruder barrel temperature is 175-190°C and the die head heating temperature is 170-190°C.

Citation Information

Patent Citations

  • Inorganic-organic composite heat stabilizer for processing polychloroethylene

    CN101412820A

  • Preparation method of functional nano calcium carbonate reinforced polyvinyl chloride resin

    CN105418813A

  • PVC (polyvinyl chloride) calcium-plastic board reinforced by modified calcium carbonate and preparation method of PVC calcium-plastic board

    CN109337243A

  • Method for preparing tin-based composite flame retardant by biomimetic synthesis technology

    CN112280102A

  • High-thermal-stability SPC floor and manufacturing method thereof

    CN113565290A